Pengaruh Ukuran Perusahaan, Laba/Rugi Operasi terhadap Audit Delay pada Perusahaan BUMN Periode 2019-2023 - Mulyati, Sri; Nurhasanah, Nunung; Hartelina, Hartelina (J-MAS (Jurnal Manajemen dan Sains), 2024)
Increasingly fierce competition on the stock exchange creates a dynamic and challenging environment for companies. To survive and thrive, companies need to adapt to changing markets, adopt new technologies, meet stringent regulations, and respond to evolving investor expectations. Financial reports are one of the mandatory requirements for stock exchange issuers to collect. The research method uses multiple regression analysis. With a sample of 38 observations (after outliers). The test uses a significant t test. The research results showed that company size cannot be proven to influence audit delay and profit/loss can be proven to influence audit delay.